THE INFLUENCE OF CITY BRANDING "SERAMBI NUSANTARA" ON TOURISTS' INTEREST AND DECISION TO VISIT IN PENAJAM PASER UTARA - Chaniago, Rizal Zainuddin; Sirait, Tongam (International Journal of Social Service and Research, 2024)
This study examines the extent to which the "Serambi Nusantara" city branding influences tourists' visiting interest and decision-making to visit Penajam Paser Utara. A sample of 400 respondents will be randomly selected using the Slovenian method to determine the sample size, and they will participate in a survey using a structured questionnaire. The findings of this research are expected to provide significant insights into the effectiveness of city branding in influencing tourist behavior and its relevance for developing improved tourism strategies in the region. The analysis results indicate that the city branding significantly affects tourists' visit interest and visit decisions with a contribution of 74.7% and 63.7%, respectively, while visit interest itself significantly influences visit decisions. This research can inform tourism marketing strategies and city branding initiatives aimed at boosting tourism in areas that may possess unique characteristics and challenges.